Modelling of tungsten erosion and deposition in the divertor of JET-ILW in comparison to experimental findings. (January 2019) - Kirschner, A.; Brezinsek, S.; Huber, A.; Meigs, A.; Sergienko, G.; Tskhakaya, D.; Borodin, D.; Groth, M.; Jachmich, S.; Romazanov, J.; Wiesen, S.; Linsmeier, Ch.; et al.
HIGHLIGHTS: Tungsten gross erosion during inter-ELM due to beryllium whereas within ELM sputtering due to deuterium dominates for JET pulse studied. Reflected beryllium from background and tungsten self-sputtering largely contribute to tungsten gross erosion. Large fraction of local tungsten deposition for inter- and intra-ELM (up to 99%) for pulse studied. Intra-ELM contribution of net erosion for the specific pulse studied about 4 times larger than inter-ELM erosion. Effective S/XB values are smaller than pure spectroscopic values. Abstract: The erosion, transport and deposition of tungsten in the outer divertor of JET-ILW has been studied for an H-Mode discharge with low frequency ELMs. For this specific case with an inter-ELM electron temperature at the strike point of about 20 eV, tungsten sputtering between ELMs is almost exclusively due to beryllium impurity and self-sputtering. However, during ELMs tungsten sputtering due to deuterium becomes important and even dominates. The amount of simulated local deposition of tungsten relative to the amount of sputtered tungsten in between ELMs is very high and reaches values of 99% for an electron density of 5E13 cm −3 at the strike point and electron temperatures between 10 and 30 eV. Smaller deposition values are simulated with reduced electron density. The direction of the B-field significantly influences the local deposition and leads to a reduction if the E × B drift directs towards the scrape-off-layer. Also, the thermal force can reduce the tungsten deposition, however, an ion temperature gradient of about 0.1 eV/mm or larger is needed for a significant effect. The tungsten deposition simulated during ELMs reaches values of about 98% assuming ELM parameters according to free-streaming model. The measured WI emission profiles in between and within ELMs have been reproduced by the simulation. The contribution to the overall net tungsten erosion during ELMs is about 5 times larger than the one in between ELMs for the studied case. However, this is due to the rather low electron temperature in between ELMs, which leads to deuterium impact energies below the sputtering threshold for tungsten.